Peningkatan Kandungan Glukosa Mikroalga Scenedesmus SP. Yang Dikultur Pada Variasi Limbah Cair Tahu Dan Intensitas Cahaya Yang Berbeda - Aisyah Sri Lestari; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Energy use still depends on petroleum energy which is non-renewable energy. As a solution, it is necessary to diversify energy other than petroleum. One of energy diversification is by utilizing microalgae as bioenergy raw material. Scenedesmus sp. is one of the microalgae which has the potential as a bioenergy feedstock. This study aims to determine optimal conditions of growth microalgae Scenedesmus sp. with the effect of the volume of tofu wastewater and different light intensities on glucose. In this research, the observation with a ratio the volume of bold basal medium and tofu liquid waste 0%, 20%, 40%, 60%, 80% and 100% and light intensity of 1000 lux, 2000 lux, 3000 lux and 4000 lux. Based on the research results obtained optimal conditions on the volume of tofu liquid waste 20% and light intensity 4000 lux with glucose 41.9 mg/L.Keywords : Scenedesmus sp., glucose, tofu liquid waste, light intensity.